FORMULATION AND EVALUATION OF ANTIFUNGAL CREAM OF CHLORPHENESIN - S., VEENA; KAUR, SURINDER; KULKARNI, GURURAJ (International Journal of Current Pharmaceutical Research, 2021)
Objective: The main aim of our research was to develop an Antifungal cream formulation consisting of Chlorphenesin for the treatment of Fungal infections. Topical route is the most suitable route for skin infections. Methods: The development of topical drug delivery systems designed to have systemic effects appears to be beneficial for a number of drugs on account of several advantages over conventional dosage forms(or) routes of drug administration. An Antifungal cream formulation consisting of Chlorphenesin was prepared. Results: The formulation was subjected to in vitro diffusion studies. Microbiological studies were performed to find out the safety of materials used in the formulation. Conclusion: The developed cream consisting of Cholrphnesin was found to be safe and effective for the treatment of fungal infection.